Half-Life Extended Nanobody-Based CD38-Specific Bispecific Killercell Engagers Induce Killing of Multiple Myeloma Cells - Hambach, Julia; Fumey, William; Stähler, Tobias; Gebhardt, Anna Josephine; Adam, Gerhard; Weisel, Katja; Koch-Nolte, Friedrich; Bannas, Peter (Frontiers in Immunology, 2022)
CD38 is a target for immunotherapy of multiple myeloma. Llama-derived CD38-specific nanobodies allow easy reformatting into mono-, bi- and multispecific proteins. To evaluate the utility of nanobodies for constructing CD38-specific nanobody-based killer cell engagers (nano-BiKEs), we generated half-life extended nano-BiKEs (HLE-nano-BiKEs) by fusing a CD38-specific nanobody to a CD16-specific nanobody for binding to the Fc-receptor on NK cells and further to an albumin-specific nanobody to extend the half-life in vivo. HLE-nano-BiKEs targeting three different epitopes (E1, E2, E3) of CD38 were expressed in transiently transfected HEK-6E cells. We verified specific and simultaneous binding to CD38 on myeloma cells, CD16 on NK cells, and to albumin. We tested the capacity of these HLE-nano-BiKEs to mediate cytotoxicity against CD38-expressing multiple myeloma cell lines and primary myeloma cells from human bone marrow biopsies in bioluminescence and flowcytometry assays with NK92 cells as effector cells. The results revealed specific time- and dose-dependent cytolysis of CD38+ myeloma cell lines and effective depletion of CD38-expressing multiple myeloma cells from primary human bone marrow samples. Our results demonstrate the efficacy of CD38-specific HLE-nano-BiKEs in vitro and ex vivo, warranting further preclinical evaluation in vivo of their therapeutic potential for the treatment of multiple myeloma.